Neoliberalism and Reconfiguration of the Diaspora in Contemporary Indonesia - Latifa, Inditian (Paradigma: Jurnal Kajian Budaya, 2019)
In most studies on globalization and transnationalism, diaspora is positioned in a conflicting and antagonistic relationship with the nation-state regime. Nevertheless, the global ascendancy of neoliberalism as a market-based mode of governing populations has brought certain changes to the relationship between the diaspora and home countries which call for further research. This essay investigates the implications of neoliberalism for diasporic kinship ties by examining emergent discourses in contemporary Indonesia that constitute an elite-led project on diasporas known as the Indonesian Diaspora Network (IDN) Global. Based on a social constructionist analysis of data gathered from activities, media reporting, and promotional materials associated with IDN Global, this essay argues that neoliberal reconfigurations of Indonesian diasporic identities manifest in two ways: unequal representation between manual workers and professionals and change of rhetoric on kinship ties as a strategic asset. Such findings reveal a more complicated and calculative relationship between the Indonesian diaspora and the Indonesian home country that complicate the valorization of diaspora against national regimes.